Use of dupilumab as adjuvant therapy in patients with previous sinus surgery for uncontrolled chronic rhinosinusitis with nasal polyps: a systematic review - Rangel-Ramírez, Gerardo J.; Sanchez-Balderas, Victor R.; Galindo-Salazar, Christian E.; Umaña-Reyes, Mauricio E. (International Journal of Research in Medical Sciences, 2025)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is an inflammatory disease of the nose and sinuses where most patients undergo surgery, however, postoperative recurrence of nasal polyps is common resulting in multiple re-interventions. Biological therapies such as dupilumab have been developed to suppress the inflammatory pathways involved in this disease. The aim of the present review is to evaluate the impact of the use of dupilumab in patients with uncontrolled CRSwNP, and its effect on the frequency of revision surgeries. A bibliographic search was performed in PubMed, Cochrane and Google Scholar. included articles published between 2019 and 2024, meta-analyses, systematic reviews, randomized controlled trials, studies in adult population, and the use of dupilumab in patients with previous sinus surgery. The quality of evidence was assessed using GRADE. Seven studies were included, totaling 1603 patients with uncontrolled CRSwNP, 84.6% of the total patients had a history of having undergone at least one surgery, after completion of follow-up, dupilumab demonstrated a reduction in the frequency of revision surgeries in addition to an improvement in sinonasal symptoms. Existing evidence supports the benefit of the use of dupilumab as an adjuvant therapy in patients with uncontrolled CRSwNP due to the reduction in the frequency of revision surgeries. Further studies addressing the effect of dupilumab in the short-term postoperative period are needed to compare the results obtained.